POTENSI TEH HIJAU DALAM PENYEMBUHAN LUKA: SISTEMATIK REVIEW - - Saryono (Universitas Muhammadiyah Semarang, 2013)
Green tea (Camellia sinensis) has been known to contain polyphenol compounds such as catechins, which have been widely studied. Especially epigallocatechin-3-gallate as a major polyphenolic compounds have the ability as an antioxidant and mineral binding agents. Green tea role in wound healing has not been known. The purpose of this systematic review is to outline the potential of green tea in wound healing. Articles obtained from electronic data bases such as PubMed, Science Direct, and Google Scholar were published from 2007 to 2013.The keywords used were: green tea and wound healing. Found 7 articles that met the inclusion criteria of 14 articles. The study showed that green tea has the potential to improve wound healing by increasing theformation of new epithelial cells, acts as an antioxidant to prevent free radical chain reaction, fibroblast proliferation and angiogenesis in the wound. Giving green tea topically to increase streng than enhance wound epithelialization of scar tissue. It can be concluded that green tea have beneficial for wound healing. It is nedeed to increase the consumption of green tea to speed up the wound healing.Keywords: green tea, wound healing, Camellia sinensis, Epigallocatechin-3-gallate